A feasibility study on the extension of the online public access catalog of the University of the Philippines Diliman Main Library to mobile phone users through SMS - Amparo, Jennifer C. (2006)
The University of the Philippines Diliman Main Library, from hereon referred to as the University Library, has always been known for being one of the pioneers in automation. It is one of the first to go on the Web to give the public access to its extensive collection thru its Online Public Access Catalog (OPAC).The author of this study believes the University Library will continue to maintain leadership in information technology in the academe through a proposal to add a Short Messaging Service (SMS) to its existing infrastructure, given the wide use of mobile phones within the campus.